Exosomal Lnc NEAT1 from endothelial cells promote bone regeneration by regulating macrophage polarization via DDX3X/NLRP3 axis - Yuxuan Chen; Yuanhao Wu; Linlin Guo; Shijie Yuan; Jiaming Sun; Kangcheng Zhao; Jiecong Wang; Ran An (Journal of Nanobiotechnology, 2023)
Abstract Background Bone regeneration is a complex procedure that involves an interaction between osteogenesis and inflammation. Macrophages in the microenvironment are instrumental in bone metabolism. Amount evidence have revealed that exosomes transmitting lncRNA is crucial nanocarriers for cellular interactions in various biotic procedures, especially, osteogenesis. However, the underlying mechanisms of the regulatory relationship between the exosomes and macrophages are awaiting clarification. In the present time study, we aimed to explore the roles of human umbilical vein endothelial cells (HUVECs)-derived exosomes carrying nuclear enrichment enriched transcript 1 (NEAT1) in the osteogenesis mediated by M2 polarized macrophages and elucidate the underlying mechanisms. Results We demonstrated HUVECs-derived exosomes expressing NEAT1 significantly enhanced M2 polarization and attenuated LPS-induced inflammation in vitro. Besides, the conditioned medium from macrophages induced by the exosomes indirectly facilitated the migration and osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs). Mechanically, Exos carrying NEAT1 decreased remarkably both expression of dead-box helicase 3X-linked (DDX3X) and nod-like receptor protein 3 (NLRP3). The level of NLRP3 protein increased significantly after RAW264.7 cells transfected with DDX3X overexpression plasmid. Additionally, the knockdown of NEAT1 in exosomes partially counteracted the aforementioned effect of Exos. The results of air pouch rat model demonstrated that HUVECs-derived exosomes increased anti-inflammatory cytokines (IL-10) and decreased pro-inflammatory cytokines (IL-1β and IL-6) significantly in vivo, contributing to amelioration of LPS-induced inflammation. Afterwards, we further confirmed that the HUVECs-derived exosomes encapsulated in alginate/gelatin methacrylate (GelMA) interpenetrating polymer network (IPN) hydrogels could promote the bone regeneration, facilitate the angiogenesis, increase the infiltration of M2 polarized macrophages as well as decrease NLRP3 expression in the rat calvarial defect model. Conclusions HUVECs-derived exosomes enable transmitting NEAT1 to alleviate inflammation by inducing M2 polarization of macrophages through DDX3X/NLRP3 regulatory axis, which finally contributes to osteogenesis with the aid of alginate/GelMA IPN hydrogels in vivo. Thus, our study provides insights in bone healing with the aid of HUVECs-derived exosomes-encapsulated composite hydrogels, which exhibited potential towards the use of bone tissue engineering in the foreseeable future.